Comparison of Standard and Intensified Regimens for HIV-Negative Adults With Tuberculous Meningitis in West China: A Retrospective Observational Study - Abdulaziz, Ammar Taha Abdullah; Ren, Yi Meng; Li, Wei; Li, Jin Mei; Zhou, Dong (Frontiers in Neurology, 2019)
Background: Tuberculous meningitis (TBM) is an extremely devastating inflammation of the central nervous system; however, to date no available optimum treatment can effectively control the disease. Method: The medical records of TBM patients from May 2011 to August 2016 in West china hospital were retrospectively analyzed. Patients were divided into three groups based on their treatment regimens (Group1: 4 standard therapy; Group2 : 3 standard drugs + levofloxacin; Group3 : 4 standard therapy + levofloxacin / Moxifloxacin); eventually the outcome was compared among all groups. Results: 202 patients with TBM were enrolled and followed up for at least 2 years. The overall outcome at 1 year, showed that 47 patients (47.5%) in G1, 10 patients (55.6%) in G2 and 48 patients (56.5%) in G3 had good prognosis; however, there was no significant difference among all groups (P=0.453); at 2 years there was also no difference among treatment groups (P=0.312). However, the full recovery rate in Group3b (4st.+Moxiflocaxin) was significantly superior to other treatment groups (P=0.002) at 1 and 2 years with P value P=0.002 and 0.027 respectively. Conclusion: The overall outcome in patients with TBM at 1 and 2 years follow up, did not show any statistically significant difference between the 4-standard chemotherapy and other intensified regimens. However, in terms of full recovery rate, the 4 standard therapy plus Moxifloxacin regimen was significantly better than other treatment regimens. Hydrocephalus was the only independent risk factor for poor prognosis.